2014
DOI: 10.1192/pb.bp.113.044396
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual worlds for role play simulation in child and adolescent psychiatry: an evaluation study

Abstract: Aims and method To develop and evaluate a novel teaching session on clinical assessment using role play simulation. Teaching and research sessions occurred sequentially in computer laboratories. Ten medical students were divided into two online small-group teaching sessions. Students role-played as clinician avatars and the teacher played a suicidal adolescent avatar. Questionnaire and focus-group methodology evaluated participants’ attitudes to the learning experience. Quantitative data were analysed using SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…Interesting gamification experiences have been developed through medical simulation games in Second Life (Toro‐Troconis and Mellström, ; Vallance et al, ). However, this study presented an academic virtual game without simulated patients, where players accessed knowledge within a competitive setting, which was useful for students' engagement and assessment (Van Nuland et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interesting gamification experiences have been developed through medical simulation games in Second Life (Toro‐Troconis and Mellström, ; Vallance et al, ). However, this study presented an academic virtual game without simulated patients, where players accessed knowledge within a competitive setting, which was useful for students' engagement and assessment (Van Nuland et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Comparing different methods of simulation, some students reporting that their experience of face-to-face simulation was enjoyable and useful as a learning tool,5 8 but medical students in a study using ‘virtual worlds’ for role play reported less anxiety and more enjoyment than face-to-face simulation 10. No studies have directly compared one type of simulation with another, so results must be seen in context and with possible response bias in mind.…”
Section: Presentationmentioning
confidence: 99%
“…Attoe et al 9 argue that more traditional non-simulation training methods ‘lack human interaction’, whereas it was found that with the use of virtual patients, fidelity could be compromised by poor graphics or limited expression of body language and it was harder to maintain concentration 10. Risk of performance-related stress for simulated patients was also acknowledged 2…”
Section: Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the second scenario we added an additional criteria to filter those applications that design IVAs with more complex intelligent and social behaviours that are used as the main character to interact with. Therefore the interaction with the VA should influence and be influenced by the user's actions and should not be limited to the role of an observer (Broome et al 2013;) (such as virtual audiences used with users with social phobias (Cornwell et al 2006)), a puppet or servant of someone else (such as a clinician speaking through an avatar (Hartanto et al 2014), avatars representing users who do not interact with other characters (Cesa et al 2013;Hall, Conboy-Hill, and Taylor 2011), or users in Second Life (second life) using an avatar to talk with the avatar of other users (Vallance et al 2014)). For the second scenario we also excluded those applications where virtual agents are used only to provoke a reaction in the user but without a long-term interaction, as in the work by Freeman et al 2014, in which the use of avatars were concentrated on representing several everyday scenes on the London underground to see how it affects the level of paranoia in some patients.…”
Section: Eligibility Criteriamentioning
confidence: 99%